DIGITALISASI PEMASARAN TEMPE KREZZ DALAM MENGHADAPI PERSAINGAN DAGANG SELAMA PANDEMI COVID-19 - Naili Fathimatuz Zakiyyah (Najah: Journal of Research and Community Service, 2023)
Indonesia is currently experiencing a crisis or disaster condition caused by the Coronavirus Disease 2019 (Covid-19) which has spread widely to the Probolinggo area. Various policies to prevent the spread of COVID-19 actually have bad implications for several other sectors, especially in the economic sector. This impact is clearly also felt by the tempe chip business actors in Sindetayar Besuk Village, such as declining sales levels and limited direct marketing methods (offline). More specifically, the purpose of this activity is to provide education and training on good and correct production processes, digital marketing of a product, and the dissemination of several digital platforms. The method used in this PKM KKN activity is Participatory Rural Appraisal (PRS) which allows community involvement in carrying out various activities, ranging from observation, providing socialization on health protocols, work sanitation and production processes, assisting the production process, assisting in making pamphlet designs, making social media accounts to product promotion and marketing. Efforts have been made to realize the marketing digitalization of "TEMPE KREZZ" materialized by the formation of WhatsApp, as digital marketing media. The community is encouraged to continue to properly manage the achievements of the activities that have been carried out in order to create a sustainable business.